Simultaneous Estimation of Piperine and 6-Gingerol in a Mixture of Piper nigrum and Gingiber officinale Through HPLC - Singh, Priyanka (Asian Journal of Chemistry, 2011)
A rapid and sensitive HPLC method has been developed for the estimation of piperine and 6-gingerol in a mixture of Piper nigrum and Gingiber officinale. The analytes were separated from the mixture by using a suitable solvent. A Kromasil C18 column provided chromatographic separation of the analytes which was followed by detection at 280 nm. This method involves extraction of analytes through simple HPLC condition with mobile phase (methanol:water) and detection through UV detector. The retention times were 05.00 and 03.27 min for piperine and 6-gingerol, respectively. The proposed method can be used for the qualitative as well as quantitative determination of the piperine and 6-gingerol in various Ayurvedic preparations such as churnas and tablets.